Ending the myth of mobility at zero costs: An external cost analysis. (March 2023) - Schröder, Daniel; Kirn, Lukas; Kinigadner, Julia; Loder, Allister; Blum, Philipp; Xu, Yihan; Lienkamp, Markus
Abstract: Although transport externalities are known to be substantial, their estimates are uncertain, especially when comparing modes. This paper presents a comprehensive approach to assess the external costs of various modes of transportation, including public transport, motorized individual transport, sharing services, and active mobility. The methodology also covers multiple external cost categories, namely air pollution, climate, noise, land use, congestion, accidents and barrier costs, as well as the health benefits of active mobility. The city of Munich, Germany, serves as a case study to calculate the total external costs of transportation per year. Furthermore, the developed approach allows the assessment of transport policy scenarios to investigate the impacts of changes in the mobility system, such as modal shifts or electrification. In Munich, diesel and gasoline cars cause almost 80% of all external costs. Increasing the active mobility share is more beneficial in terms of external cost reductions than increasing the public transport share or electrification rate.